The Value of Local Wisdom in the Practice of Fine Fee Treatment at the Mosu`sa Festival, Traditional of the Kaili Da`a Inland Tribe - Rahayu Indriasari; Andi Mattulada; Abdul Pattawe; Jurana N.S; Latifah Sukmawati Yuniar; Nurhaja Djasman; Andi Selviani; Mia Lestari Sangadji (AMCA, 2026)
This study aims to reveal the practice of the treatment of fine costs at the Mosu'Sa Traditional Festival of the Kaili Da'a Inland Tribe, Kaliburu Village, Sindue Tombusabora District. Donggala Regency, Central Sulawesi. This research is a qualitative study with ethnographic study analysis techniques. The results of the study found that the traditional festival is not only about the costs in implementing the traditional festival but there is another burden that is an additional burden, namely the cost of customary fines that can occur in the process of implementing the traditional mosu`sa festival due to customary violations. The practice of the treatment of fine costs in the Da'a inland tribe, especially in Kaliburu Village, is about honor, responsibility, and solidarity of one tribe.